Inclusion of Sub-Antarctic Macroalgae (Gigartina skosttsbergii) as Feed Ingredient for Grazing Sheep - Cinthya Glucevic; Navid Ghavipanje; Lizbeth E. Robles-Jimenez; Sergio Radic-Schilling; Manuel Gonzalez Ronquillo (Animals)
Two experiments were carried out to evaluate the inclusion impacts of macroalgae Gigartina skottsbergii (Gs) for grazing sheep. Experiment (Exp.) 1 studied the effect of Gs on in vitro gas production (IVGP), dry matter (DM) digestibility (IVDMD), and methane (CH4) emission using three fistulated sheep and 96 h incubation of samples. In Exp. 2, ten Dohne Merino ewes [5-year-old; 47 ± 0.14 kg body weight (BW)] were randomly assigned to dietary treatments supplemented with Gs at 0 or 450 g DM/d per animal. The study lasted 31 days and was preceded by an adaptation period of 9 days. The BW, body conditional score (BCS), and blood were sampled at the first and the last day of the trial. The results of Exp. 1 showed that Gs supplementation reduced (MCP, p = 0.026) gas production (A), lag time (p = 0.013), and IVDMD (p = 0.071), while it enhanced partition factor (PF96; p = 0.004) and microbial crude protein (MCP) (p = 0.054). The concentration of CH4 decreased after 3 h (p = 0.0002), 6 h (p = 0.013), and 12 h (p = 0.010) with a tendency at 9 h (p = 0.109) and 24 h (p = 0.068). In Exp. 2, there were no diet effects on the initial BW (IBW, p = 0.77), final BW (FBW, p = 0.91), and average daily gain (ADG, p = 0.24) of ewes; however, Gs supplementation decreased BCS (p = 0.004). Of all blood parameters, only the concentration of glucose (p = 0.021) and albumin (p = 0.011) decreased in the Gs group. Overall, our results revealed that the dietary inclusion of Gs (at 450 g DM/d) affected neither the BW nor ADG of ewes; however, Gs was accompanied by lesser IVGP and CH4 emission.